2018
DOI: 10.1002/jcb.27792
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin combined with MCC950 to treat multiple sclerosis in experimental autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS) is a highly disabling demyelinating disease, which mainly affects young adults and is difficult to cure. Activated microglia may be involved in the process of neuronal cell damage and release inflammatory cytokines to injure neurons. Rapamycin (RAPA), an immunosuppressant, can induce autophagy in microglia to delay the process of the disease. As an inhibitor of NLRP3, MCC950 (CP‐456773) can regulate the activation of inflammasome. An experimental autoimmune encephalomyelitis model, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…MCC950 improved allodynia threshold in a murine model of RRMS and attenuated relapses [97]. A later study investigated the value of a rapamycin-MCC950 combination and found that MCC950 enhanced the activity of rapamycin (immunosuppressant) and that this combination was effective in mitigating MS symptoms and cytokine release [98]. IC100 is the most recently developed inflammasome inhibitor and is a humanized antibody developed against the ASC component of inflammasomes, thus having the ability to inhibit several inflammasomes including NLRP1, NLRP3, NLCR4 and AIM2.…”
Section: Inflammasomes As Drug Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCC950 improved allodynia threshold in a murine model of RRMS and attenuated relapses [97]. A later study investigated the value of a rapamycin-MCC950 combination and found that MCC950 enhanced the activity of rapamycin (immunosuppressant) and that this combination was effective in mitigating MS symptoms and cytokine release [98]. IC100 is the most recently developed inflammasome inhibitor and is a humanized antibody developed against the ASC component of inflammasomes, thus having the ability to inhibit several inflammasomes including NLRP1, NLRP3, NLCR4 and AIM2.…”
Section: Inflammasomes As Drug Targetsmentioning
confidence: 99%
“…MCC950 improved allodynia threshold in a murine model of RRMS and attenuated relapses [ 97 ]. A later study investigated the value of a rapamycin-MCC950 combination and found that MCC950 enhanced the activity of rapamycin (immunosuppressant) and that this combination was effective in mitigating MS symptoms and cytokine release [ 98 ].…”
Section: Inflammasomes As Drug Targetsmentioning
confidence: 99%
“…On the other hand, studies in humans showed that autophagy activity is not increased in neither the peripheral nor brain-circulating CD4+ T cells of MS patients compared with controls, despite having increased Atg5 gene and protein levels [254]. Other studies centered on the role of microglia-related inflammation suggest that autophagy induction via mTOR inhibition contributes to reducing both demyelination and inflammation in EAE [255]. As far as it concerns neurodegenerative disorders, autophagy induction seems to play a beneficial effect in counteracting acute and chronic inflammation [256].…”
Section: Autophagy and Proteasome Linking Altered Immunity And Synmentioning
confidence: 99%
“…As autophagy can have both beneficial [ 257 ] and deleterious [ 258 ] effects depending on the disease context [ 252 ], we should be very cautious when interpreting the global effects of autophagy-targeting treatment because it could be cell- and time-specific. We already observed that the aberrant autophagy activity (downregulation or hyperactivation) that occurs in pathological settings is not a general feature that equally affects all organs or tissues of any individual [ 259 ].…”
Section: Therapeutic Approach To Npslementioning
confidence: 99%